2020
DOI: 10.1210/clinem/dgaa958
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Upregulation and Antiviral Immune Responses in Graves Disease

Abstract: Context The origin of Graves disease (GD) remains elusive. However, evidence of an association between GD and viral infections is emerging. Human leukocyte antigen (HLA) class I presents viral antigens to circulating immune cells and plays a crucial role in the defense against viral infections. Objective This work aimed to investigate HLA class I expression, enterovirus presence, and the viral immune response proteins signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In human thyroid, viral infection has also been shown to activate interferon signaling and the expression of interferon-stimulated genes (36,49). Moreover, enhanced expression of HLA class I and of interferon-related STAT1 and PKR genes has been demonstrated in the thyroid tissue collection used in this study (9,10).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In human thyroid, viral infection has also been shown to activate interferon signaling and the expression of interferon-stimulated genes (36,49). Moreover, enhanced expression of HLA class I and of interferon-related STAT1 and PKR genes has been demonstrated in the thyroid tissue collection used in this study (9,10).…”
Section: Discussionmentioning
confidence: 72%
“…Enteroviruses (9)(10)(11), parvovirus B19 (12)(13)(14) and hepatitis C virus (HCV) (15,16) have all been associated with AITD. Among herpesviruses, Epstein-Barr virus (EBV) has been associated with GD (17)(18)(19), while human herpes virus 6 (HHV-6) and cytomegalovirus (CMV) may be associated with both HT and GD (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also examined the relationship between COVID-19 and HLA in patients with certain diseases, such as cancer. For example, no significant allelic relationship was found in the HLA genotype of lung cancer patients with and without COVID-19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown an association between various diseases and certain HLA alleles, including those caused by ribonucleic acids (RNA) viruses, such as SARS, influenza, human immunodeficiency virus (HIV), hepatitis C, rabies, and other [ 23 ]. Compared with HLA class II, HLA class I plays a crucial role in viral infection by presenting viral antigens to CD8 + T cells on the surface of infected cells, followed by recognition and destruction of the cells [ 24 ]. The likely effect of T cells in SARS-CoV-2 infection could be illustrated by the response of 40–60% of T cells in unexposed individuals to viral proteins due to a cross-immune reaction with other coronaviruses in previous colds [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in many cases further studies are needed to confirm whether the expression alone is the predisposing factor and how the regulatory variation affects differential expression in diseases. Elevated HLA expression levels have been associated with inflammatory bowel diseases ( 56 , 76 ), scleroderma patients with interstitial lung disease ( 77 ), ankylosing spondylitis ( 78 ), Graves’ disease ( 79 ), systemic lupus erythematosus ( 80 ), rheumatoid arthritis ( 72 ), and multiple sclerosis ( 81 ). Additionally, in celiac disease and type 1 diabetes, higher expression of DQA1*05 and DQB1*02 alleles was found in patients when compared to healthy controls ( 82 , 83 ).…”
Section: Hla Expression In Human Diseasesmentioning
confidence: 99%